CREATING THE “SERBIAN WORLD”: QUALITATIVE CONTENT ANALYSIS OF PUBLIC STATEMENTS REGARDING THE CONCEPT AND DEFINING ITS DIMENSIONS - Ljubomirović, Aleksandar (National interest, 2024)
This article sets out to present selected outcomes of the author’s research on the dimensions of the “Serbian world” concept. Although the term has indeed become quite popular in the public discourse, the concept per se has not been part of academic discussions. Therefore, this paper sets out to analyse the content of the afore-mentioned concept and introduce it into the scientific framework. The methodology used in this paper includes a qualitative content analysis of the public statements regarding the Serbian world concept, which are available and published, first and foremost, in domestic media outlets. At the same time, the analysis of the concept is limited to observing its various dimensions, using the statements of Serbian officials as examples of discursive shaping and construction of each of the separate dimensions. Based on the carried-out research, the concept is founded on the idea of creating a supranational Serbian civilization based on ancient models. This community would unite all Serbs, the Serbian diaspora, but also all those people simply learning Serbian or identifying with its values, and declaring an attachment to Serbian culture. Besides its territorial dimension, which has so far prevailed in public discourse especially among its opponents, the Serbian world also resides on national, psychosocial and cultural components, while the main ethnos in the concept is certainly the Serbian nation, around which other ethnic groups should gather. Moreover, nationality-related, psychosocial and cultural dimensions are also supposed to be important aspects according to the discourse participants. The last component would be the Orthodox religion which is supposed to be one of the main pillars and an important co-constituent of the Serbian world concept. Finally, perspectives for further analysis of the concept were also presented in this paper.